1982
DOI: 10.1111/j.1471-0528.1982.tb04661.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma noradrenaline and adrenaline levels in normal pregnancy and in pregnancy‐induced hypertension

Abstract: Plasma concentrations of noradrenaline and adrenaline were measured serially during normal pregnancy in 52 women who remained normotensive and in nine who developed pregnancy-induced hypertension but were otherwise normal. There was a significant fall in both noradrenaline (P and adrenaline (P<0.05) levels during normal pregnancy. Throughout pregnancy the mean levels of both catecholamines were lower in the patients who developed pregnancy-induced hypertension than in the normotensive patients. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Prior studies on plasma catecholamines have been conflicting: observations have reported unchanged (24,39), increased (40), or decreased (22,23) catecholamine levels during pregnancy compared to nonpregnancy. We observed an increased plasma norepinephrine during the second trimester of pregnancy at baseline and during posture study, which was most pronounced during the third trimester.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies on plasma catecholamines have been conflicting: observations have reported unchanged (24,39), increased (40), or decreased (22,23) catecholamine levels during pregnancy compared to nonpregnancy. We observed an increased plasma norepinephrine during the second trimester of pregnancy at baseline and during posture study, which was most pronounced during the third trimester.…”
Section: Discussionmentioning
confidence: 97%
“…In healthy pregnant women, plasma and urinary catecholamine levels are not or only slightly increased (12)(13)(14)(15)(16). Even in pre-eclampsia, plasma catecholamine levels are only slightly elevated.…”
Section: Introductionmentioning
confidence: 96%
“…The whole-day values of urinary NE excretion from the G1, working period, to the G4, non-working period, were consistently declined. The NE levels in serum or in urine during pregnancy are on controversy such as increased 33) , decreased 34) or not changed 29) . None of these reports, however, referred to the relationship between NE level and workload of pregnant shift workers.…”
Section: Nementioning
confidence: 99%